The Development of L2 Interactional Competence A Multimodal Study of Complaining in French Interactions - Skogmyr Marian, Klara (Routledge Advances in Second Language Studies, 2023)
This book presents unique insights into the development of L2 interactional competence through the lens of complaining, demonstrating how a closer study of complaining as a social activity can enhance our understanding of certain aspects of language learning with implications for future L2 research. The volume employs a multimodal, longitudinal conversation analytic (CA) approach in its analysis of data from video-recorded interactions of several elementary and advanced L2 speakers of French as they build their interactional competence, understood as the ability to accomplish social actions and activities in the L2 in context-dependent and recipient-designed ways. Skogmyr Marian calls attention to three key dimensions of complaining in these conversations - its structural organization, the interactional resources people use when they complain, and how speakers' shared interactional histories and changing social relationships affect complaint practices. The volume underscores the fundamentally multimodal, socially situated, and co-constructed nature of L2 interactional competence and the socialization processes involved in its development, indicating paths for new work on interactional competence and L2 research more broadly. This book will be of appeal to students and scholars interested in second language acquisition, social interaction, and applied linguistics.